Study of Aromatic and Medicated Plants in Uttrakhand, India: With Focus on Role in Employment Generation and Supply Chain Management - Pangriya, Ruchita (International Journal of Social Sciences and Management, 2015)
India is one of the major exporters of crude drugs including Medicated and Aromatic Plants globally. As per the latest and most recent data available, in 2012-2013 India’s total export of Ayush, Medicinal herbs and their value added products was USD 395.58 million. State of Uttarakhand in India is a natural habitat of the prosperous varieties of herbs, medicinal and aromatic plant species. The Government of Uttarakhand state has also realised this big potential and is continuously trying to tap this wealth. In 2012-2013 the state exported culinary herbs, Aromatic products and medicated products worth ` 29.0 crore. The aim of this study of MAP products in Uttarakhand state is to evaluate the impact of cultivation of MAP products, in relation to the new employment generation and also to study the supply chain management in context to the activities of various agencies engaged in collection, distribution and auction. This paper focuses on the cultivation program running in Uttrakhand by HRDI and its importance in employment generation in the hilly districts. It is very evident in today’s time that a strong supply chain is basic necessity for every organised business to sustain and to be successful in long run. This paper also studies the existing supply chain for MAP products and investigates the loopholes for further improvement so that the cultivators of MAP get maximum monetary benefits with minimum problems. In addition to that, role of different corporations like KMVN, GMVN and Bhesaj Corporation in marketing of these MAP products has also been discussed under the presented study. DOI: http://dx.doi.org/10.3126/ijssm.v2i2.12396 Int. J. Soc. Sci. Manage. Vol-2, issue-2: 148-156